A scoping review of international virtual knowledge exchanges for healthcare professionals. Issue 1 (2nd January 2023) - Bridgwood, Bernadeta; Woolley, Kate; Poppleton, Aaron
ABSTRACT: International knowledge exchanges within healthcare have historically been a popular method to provide exposure to practice in other national and international healthcare settings. As the COVID-19 pandemic forced many countries into lockdowns, knowledge exchanges in healthcare were forced into a period of suspension. This provided an opportunity to consider alternative methods of delivery. This scoping review explores virtual knowledge exchanges in healthcare professional education, including their format and related outcomes. Thirty-four virtual knowledge exchanges were identified. These demonstrated viability and subjective participant satisfaction. Virtual methods removed barriers of time, distance and finance associated with traditional exchanges, while still facilitating engagement with other international healthcare colleagues. However these exchanges were heterogeneous in their aims, structure and theoretical underpinnings. An understanding of educational outcomes and their measurement was not always obvious. Applying an overlay of robust pedagogical theory would strengthen and provide structure to the clearly well valued activity of international exchange.